2004
DOI: 10.1007/bf03018542
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam causes less sedation in volunteers with red hair

Abstract: P Pu ur rp po os se e: : We studied sedation, cognition, and mood during midazolam infusion in volunteers with red and non-red (blond or brown) hair, to test the hypothesis that patients with red hair may require more drugs to attain desired levels of sedation.M Me et th ho od ds s: : Twenty red and 19 non-red hair subjects were studied in a randomized, placebo-controlled cross-over design. Subjects were studied during placebo and midazolam at 30 ng·mL -1 target effect site concentration. Sedation was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 26 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…2,3 In a randomized placebo-controlled crossover trial, midazolam administration produced less sedation and cognitive impairment in red-haired subjects than in control subjects. 2 Red-haired female volunteers showed increased sensitivity to thermal pain and decreased efficacy of the local anesthetic agent, lidocaine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 In a randomized placebo-controlled crossover trial, midazolam administration produced less sedation and cognitive impairment in red-haired subjects than in control subjects. 2 Red-haired female volunteers showed increased sensitivity to thermal pain and decreased efficacy of the local anesthetic agent, lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In a randomized placebo-controlled crossover trial, midazolam administration produced less sedation and cognitive impairment in red-haired subjects than in control subjects. 2 Red-haired female volunteers showed increased sensitivity to thermal pain and decreased efficacy of the local anesthetic agent, lidocaine. 3 While these results suggest patients with red hair may recover from anesthesia faster and suffer more severe postoperative pain than those without red hair, a study in surgical patients did not find any difference in the time to recovery after surgery or the severity of postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…The gene associated with "red hair" on chromosome 4 is proximal to a cluster of genes associated with fibrinogen (25), and there has long been anecdotal belief that patients with red hair color exhibit decreased coagulation / increased risk of hemorrhage during surgical procedures (3,5,10). In a recent study comparing nine red-haired women with nine "dark"-haired women (all Caucasian and comparable in height, weight, and age), the red-haired women exhibited a significant decrease in platelet function but no absolute differences in platelet numbers or coagulation factors (4).…”
Section: Discussionmentioning
confidence: 99%
“…Women with naturally red hair have been hypothesized to have altered coagulation (3)(4)(5) and immune function (6,7). Cross-sectional studies have suggested that the proportion of women with naturally red hair is greater among those with endometriosis compared with the general population (8 -10).…”
mentioning
confidence: 98%
“…It is important to keep in mind the considerable variability among patients with respect to the most important issues and optimal choices in pharmacologic management, based on such factors as age and organ dysfunction. There is emerging evidence that genetic variability exists for relative susceptibility to opioids [ 37 ] and probably for other important drug classes [ 38 ]. In addition, the patient's condition typically changes over the course of ICU hospitalization, as do the targets for analgesia and sedation.…”
mentioning
confidence: 99%